Regulatory and legal basement of decentralization in local self-government according to the legislation of Ukraine and Poland - Shatilo V. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of the article is to compare the regulatory and legal basement of decentralization in Ukraine and Poland. Also the purpose of the article includes the definition of common and distinctive features of legal provisions of decentralization in Ukraine and Poland. Methodology.The methodology consists of legal comparison of scientific-theoretical and regulatory materials. The author used such methods of scientific knowledge: dialectical, systematic, historical methods and methods of analysis, synthesis and analogy. Result: the article devotesthe development of regulatory and legal basement ofdecentralization in Poland and Ukraine. It is characterized by the following common features: 1) the presence of a long transition period from self-government of a state with experience in an undemocratic regime; 2) the foundation in the form of the European Charter of Local Self-Government of 1985; 3) carrying out the reform of the decentralization of public power in the context of EU values, but outside the fulfillment of the requirements for joining the specified state-political association. Among the distinguishing features, first of all, it is necessary to mention different approaches to the meaningful filling of normative and legal acts that implemented the reform of local self-government, including conceptual ones: 1) if in Ukraine local self-government is the right of a territorial community, then in Poland it is its duty ; 2) non-segregation of agricultural territorial communities, similar to Polish legislation. In addition, unlike Poland, whose Constitution reflects legislative changes due to the reform of local self-government with a view to decentralization, these changes have not been made to the Constitution of Ukraine due to the martial law in Ukraine. The development of decentralization in local self-government both in Ukraine and Poland consists of two periods: posttotalitarian (postsoviet) and preparation to admittance for EU membership. Originality. It was established that the reform of the decentralization of public power in both Ukraine and Poland was carried out in the context of EU values, but outside of the requirements for joining the specified state-political association. The fact is that the reform of decentralization in both Ukraine and Poland reflectes the idea that local self-government is the fundamental basis of the modern highly developed democratic states. Practical significance. The results of the research can be used in law-making and scholar activities.